PROTEIN SIGNATURES OF EXTREME OLD AGE AND LONGEVITY. (11th November 2018) - Sebastiani, P; Monti, S; Morris, M; Gurinovich, A; Glass, D; Jennings, L; Perls, T T
Abstract: We used a high-throughput Somascan platform to quantify 4785 proteins in serum of 224 centenarians, offspring, and controls (mean ages: 105, 80, 79) from the New England Centenarian Study, and conducted various analyses to identify protein sets that change with extreme old age. We identified almost 1300 proteins that differed between centenarians, their offspring, and controls (p-value<10–6), and include many well-known genes such as growth hormone receptor and insulin genes, as well as novel aging markers. Protein set enrichment analysis identified many pathways that are downregulated (MTORC1, androgen response), or upregulated (heme metabolism) in centenarians compared to younger age groups. To distinguish protein signatures caused by extreme old age from those facilitating extreme longevity we searched for protein sets that distinguish between short and long survival within various age groups. We identified approximately 30 markers of extreme survival independent of age that, if validated, could become biomarkers of healthy aging.